2018
DOI: 10.1016/j.foodcont.2018.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Seafood products notifications in the EU Rapid Alert System for Food and Feed (RASFF) database: Data analysis during the period 2011–2015

Abstract: Over the years, the EU has sought to strengthen its food safety policy by reorganizing and enforcing official control activities within its territory and throughout the food chain (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 22 publications
(28 reference statements)
0
26
0
1
Order By: Relevance
“…Pigłowski (), relating to pathogenic microorganisms, noticed that in 1980–2017, more frequently notified were Salmonella sp., Listeria , Escherichia, and Vibrio in products of animal origin: meat, poultry, milk, and seafood (fish, crustaceans and mollusks). D'Amico et al () also indicated pathogenic microorganisms among two main reasons for the RASFF notifications in bivalve mollusks in 2011–2015. This kind of hazard concerned also products of nonanimal origin: fruits, vegetables, herbs, spices, and nuts (Pigłowski, ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Pigłowski (), relating to pathogenic microorganisms, noticed that in 1980–2017, more frequently notified were Salmonella sp., Listeria , Escherichia, and Vibrio in products of animal origin: meat, poultry, milk, and seafood (fish, crustaceans and mollusks). D'Amico et al () also indicated pathogenic microorganisms among two main reasons for the RASFF notifications in bivalve mollusks in 2011–2015. This kind of hazard concerned also products of nonanimal origin: fruits, vegetables, herbs, spices, and nuts (Pigłowski, ).…”
Section: Discussionmentioning
confidence: 98%
“…Similar elements (cadmium, mercury, and lead) were also indicated as a cause of the notifications in 2003–2007 by Kleter et al (). D'Amico et al () indicated heavy metals as the main reason for the RASFF notifications in seafood (fish and cephalopods) in 2011–2015. Similarly, they noticed that seafood was notified mainly by Italy and Spain and originated from these two countries, followed by Vietnam and Morocco.…”
Section: Discussionmentioning
confidence: 99%
“…They stated that Salmonella spp. was reported in bivalve molluscs and crustaceans, Listeria monocytogenes in fish and crustaceans, Escherichia coli in bivalve molluscs and Vibrio in crustaceans [24]. However, notifications related to pathogenic microorganisms in seafood were also signaled by other authors: Salmonella spp., Listeria monocytogenes and Vibrio in frozen fish in 2005–2010 [25], Salmonella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Spain is even a large exporter, mainly to EU, that adsorbs twothirds of its exports of which 20% were addressed to Italy (Eurofish, 2017), in accordance with the outcomes of this study. However, as recently highlighted by D' Amico et al (2018), products of Spanish origin are often made with raw materials coming mainly from South America and Asia.…”
Section: Data Collection and Analysismentioning
confidence: 99%